Features of Mathematical Modeling of the Thermal State of the Bulb Type Hydrogenerators - Tretiak, Oleksii; Shut, Olexandr; Gakal, Pavlo; Poliienko, Vladyslav Ruslanovych (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
The analysis of different Hydrogenerators designs was carried out. The advantages and lacks of various versions of the design arrangement depending upon action of different nature forces were shown. Calculation studies in three-dimensional model statement to determine the thermal state of the bulb type Hydrogenerators were carried out. The opportunity of carrying out of three-dimensional calculation of the thermal state of the bulb type Hydrogenerators with air cooling is submitted. The study of the turbine type influence to the stressed state of the generator was carried out. In the article the special attention is paid to application of various calculation methods namely the method of detailed thermal (equivalent) diagrams; Analytical solution of the thermal state; Methods of CFD (computational fluid dynamics) of finite elements. It is shown that the application of CFD (computational fluid dynamics) methods is possible with the addition of existing limiting conditions. Initial and limiting conditions for calculation of complicated stressed components of the design were determined. For the first time the calculation of the thermal state of the bulb Hydrogenerators taking into account the basic and additional parameters was carried out and verified. The results shall help improve the reliability of hydro- power plants and the power system as a whole.